Garantism and judicial reasoning - García Martínez, Oscar Isaac (2022)
The theoretical vestiges of the paleo-positivist positions have had as a direct consequence a vehement exaltation of the fact of turning into positive any type of content that is argued as a fundamental right, alleging with it an adequate constitutional regulation that, in the end, serves as a justifying discourse for State domination. Accordingly, it is important to analyze theoretical positions, such as the rights-based one, that help us to understand not only how to materialize the progress made in terms of protection of fundamental rights, but also to reflect on and criticize the activity of the legal system in its entirety, since it has a notoriously power undermining role. Thus, we will be able to account, with this epistemic starting point, how the very modification of the different normative statements, as well as the decision-making function of the judge, is conditioned thanks to the substantive contents of the constitutional rules.